Negotiating the Korea-Singapore FTA : a case study - Kesavapany, K. (Gale virtual reference library, 2007)
Analyses and documents the rationale behind the Korea-Singapore Free Trade Agreement and its impact on the economies of Korea and Singapore, underpinning the growing economic linkages between the two countries that have become stronger since the enforcement of the agreement.